Comparison of Greenhouse Gas Offset Quantification Protocols for Nitrogen Management in Dryland Wheat Cropping Systems of the Pacific Northwest - Brown, Tabitha T.; Lee, Carrie M.; Kruger, Chad E.; Reganold, John P.; Huggins, David R. (Frontiers in Environmental Science, 2017)
In the carbon market, greenhouse gas (GHG) offset protocols need to ensure that emission reductions are of high quality, quantifiable and real. Lack of consistency across protocols for quantifying emission reductions compromise the credibility of offsets generated. Thus, protocol quantification methodologies need to be periodically reviewed to ensure emission offsets are credited accurately and updated to support practical climate policy solutions. Current GHG emission offset credits generated by agricultural nitrogen (N) management activities are based on reducing the annual N fertilizer application rate for a given crop without reducing yield. We performed a “road test” of agricultural N management protocols to evaluate differences among protocol components and quantify nitrous oxide (N2O) emission reductions under sample projects relevant to N management in dryland, wheat-based cropping systems of the inland Pacific Northwest (iPNW). We evaluated five agricultural N management offset protocols applicable to North America: two methodologies of American Carbon Registry (ACR1 and ACR2), Verified Carbon Standard (VCS), Climate Action Reserve (CAR), and Alberta Offset Credit System (Alberta). We found that only two protocols, ACR2 and VCS, were suitable for this study, in which four sample projects were developed representing feasible N fertilizer rate reduction activities. The ACR2 and VCS protocols had identical baseline and project emission quantification methodologies resulting in identical emission reduction values. Reducing N fertilizer application rate by switching to variable rate N (sample projects 1-3) or split N application (sample project 4) management resulted in a N2O emission reduction ranging from 0.07 to 0.16 and 0.26 Mg CO2e ha-1, respectively. Across the range of C prices considered ($5, $10, and $50 per metric ton of CO2 equivalent), we concluded that the N2O emission offset payment alone ($0.35 to $13.0 ha-1) was unlikely to encourage a change in fertilizer N management; however, the fertilizer cost savings from adopting variable or split N management would incentivize adopting these practices. Therefore, the monetary incentive of adopting agricultural N management BMPs for reducing N2O emission should be tied to other co-benefits and existing conservation programs to encourage N rate reductions that do not limit yield, crop quality, or economic stability.